Distinct Contribution of the HtrA Protease and PDZ Domains to Its Function in Stress Resilience and Virulence of Bacillus anthracis - Israeli, Ma’ayan; Elia, Uri; Rotem, Shahar; Cohen, Hila; Tidhar, Avital; Bercovich-Kinori, Adi; Cohen, Ofer; Chitlaru, Theodor (Frontiers in Microbiology, 2019)
Anthrax is a lethal disease caused by the gram-positive spore-producing bacterium Bacillus anthracis. We previously demonstrated that disruption of htrA gene, encoding the chaperone/protease HtrABA (High Temperature Requirement A of B. anthracis) results in significant virulence attenuation, despite unaffected ability of htrA strains (in which the htrA gene was deleted) to synthesize the key anthrax virulence factors: the exotoxins and capsule. B. anthracis htrA strains exhibited increased sensitivity to stress regimens as well as silencing of the secreted starvation-associated Neutral Protease A (NprA) and down-modulation of the bacterial S-layer. The virulence attenuation associated with disruption of the htrA gene was suggested to reflect the susceptibility of htrA mutated strains to stress insults encountered in the host indicating that HtrABA represents an important B. anthracis pathogenesis determinant. As all HtrA serine proteases, HtrABA exhibits a protease catalytic domain and a PDZ domain. In the present study we interrogated the relative impact of the proteolytic activity (mediated by the protease domain) and the PDZ domain (presumably necessary for the chaperone activity and/or interaction with substrates) on manifestation of phenotypic characteristics mediated by HtrABA. By inspecting the phenotype exhibited by htrA strains trans-complemented with either a wild-type, truncated (PDZ), or non-proteolytic form (mutated in the catalytic serine residue) of HtrABA, as well as strains exhibiting modified chromosomal alleles, it is shown that (i) the proteolytic activity of HtrABA is essential for its N-terminal autolysis and subsequent release into the extracellular milieu, while the PDZ domain was dispensable for this process, (ii) the PDZ domain appeared to be dispensable for most of the functions related to stress resilience as well as involvement of HtrABA in assembly of the bacterial S-layer, (iii) conversely, the proteolytic activity but not the PDZ domain, appeared to be dispensable for the role of HtrABA in mediating up-regulation of the extracellular protease NprA under starvation stress, and finally (iv) in a murine model of anthrax, the HtrABA PDZ domain, was dispensable for manifestation of B. anthracis virulence. The unexpected dispensability of the PDZ domain may represent a unique characteristic of HtrABA amongst bacterial serine proteases of the HtrA family.